P277 Reducing HIV self-testing barriers in black african communities using collect: a PHE HIV innovation fund project. (14th July 2019) - Halfin, George; Howells, Will; Mukiwa, Takudzwa; Edwardes, Dominic; Logan, Louise; Kifetew, Chamut
Abstract : Background: Black Africans (BA) are disproportionately affected by HIV in England, comprising 38% of heterosexuals diagnosed in 2017, 57% of whom were diagnosed late. Late diagnosis was even higher in BA men (69%). HIV self-testing is a preferred way to test among BA (Sigma, 2015). Despite increasing online availability of self-tests, Terrence Higgins Trust(THT) noted a lower uptake amongst BA than others. One reason provided includes a reluctance to receive kits in shared accommodation. With public funding, we added Click&Collect delivery to explore if this would help reduce HIV self-testing barriers. Methods: 20, 000 self-tests offered online to key communities, including BA, from October–December 2018. Click&Collect option provided, with 4, 000+ collection points. While open to all, enhanced promotion went to BA. Users were sent two follow-up SMSs requesting results. All those with a reactive result received THT support calls. A user survey assessed reasons for using the service. Results: 18, 597 tests dispatched; 3, 291 to BA. 50% BA reported results, compared to 61% overall. Click&Collect uptake: 10% overall; 18% BA men. 11 BA reported reactive results, one of whom used Click&Collect. The reactivity rate for BA was 0.7%. From the user survey: Over 48% of Click&Collect users stated primary reasons for choosing it were not wanting anyone they lived with accidentally opening package, or finding out they were taking an HIV test. 50% of BA Click&Collect users chose self-test for confidentiality – compared to 34% of all other Click&Collect users, for whom it was not a top reason. Conclusion: Click&Collect may address privacy/confidentiality issues for BA where this is a primary issue. The proportion of BA men using Click&Collect was higher than in other groups. As self-testing services increase, Click&Collect offers a way to increasing HIV testing uptake in a group highly affected by late diagnosis. Disclosure: No significant relationships.